Konsep Kepemimpinan Negara Islam (Studi Komparasi Pemikiran al-Mawardi dan Ibnu Taimiyah) - Kasman Bakry; Abdul Haris Abbas; Ashar; Abdullah Nazhim Hamid (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The objectives of this study is to explore and compare the concept of leadership in an Islamic state according to Ibn Taimiyah and al-Mawardi. This study is a qualitative descriptive comparative study, with normative, conceptual, and historical approach. The result os study reveals that Ibn Taymiyyah pays more attention to the ultimate goal of a state leadership, namely the benefit of the world and the hereafter, while al-Mawardi is more concerned with the government system in the form of imÄmah or khilÄfah.